Identification of resistant source for leaf webber/capsule borer, Antigastracatalaunalis Duponchel (Lepidoptera: Crambidae) in sesame: IDENTIFICATION OF RESISTANT SOURCE FOR LEAF WEBBER/CAPSULE BORER IN SESAME - T BOOPATHI; K T RAMYA; A L RATHNAKUMAR (Journal of Oilseeds Research, 2023)
The incidence ofthe leaf webber/capsule borer, Antigastra catalaunalis Duponchel (Lepidoptera:Crambidae) is common during vegetative, flowering and pod formation stages of sesame during two seasons. The sesame genotypes (n=60) were screened for A. catalaunalis during two season 1 and 2. In season 1, four genotypes, SES-K-20-2010, SES-K-20-3002, SES-K-20-1062 and SES-K-20-2022 were found free from A. catalaunalis incidence. The sesame genotypes (n=60) graded for A. catalaunalis as highly resistant (15 genotypes), resistant (12 genotypes), moderately resistant (15 genotypes), susceptible (6 genotypes) and highly susceptible (12 genotypes) based on incidence. In season 2, none of genotype was found free from A. catalaunalis incidence. The sesame genotypes (n=60) graded for A. catalaunalis as highly resistant (1 genotype), resistant (17 genotypes), moderately resistant (28 genotypes), susceptible (13 genotypes) and highly susceptible (1 genotype) based on incidence. To summarize, 16 genotypes were highly resistant to A. catalaunalis and the resistant genotypes can be used as donor in future breeding programmes.